THE EFFECTS OF TEACHING TECHNIQUES TOWARDS STUDENT’S READING SKILL AT VOCATIONAL HIGH SCHOOL IN SOUTH JAKARTA - Ferdias Prihatna Sari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2022)
The purpose of this study was to: determine the interactional effects of teaching technique towards student’s reading skill that was taught by role plays and filling information gap (both are communicative language teaching) to the students. The research method used was experimental one. Sample size of 60 students consisting of 30 for experimental class and 30 for control class taken from Vocational High School in South Jakarta, and the sampling technique used is cluster sampling. Research instruments used were the test to distinguish the effect of teaching techniques towards student’s reading skill in the form of oral test (5 items for scoring), that have been tested valid and reliable with coefficient of reliability at 0.839 and 0.705. The research uses two-ways ANOVA test. The result showed there is a significant effect of teaching technique towards student’s reading skill, as Fobserved = 95.553 > Ftable = 2.77 and Sig = 0.000 < 0.05. The results contribute most to the increasing of student’s reading skill.